An integrated approach to strategy implementation in the Limpopo Department of Roads and Transport - Boshielo, Paulina Shela Polly (University of Limpopo (Turfloop Campus), 2008)
This research report is based on an integrated approach to strategy implementation in the Limpopo Department of Roads and Transport. The purpose of this research was to investigate which factors are key in the implementation of strategies and how can they be integrated to achieve the stated goals of the Limpopo Department of Roads and Transport. This report included both qualitative and quantitative research methods. The major finding of the study was that there are four key drivers of strategy implementation. These key drivers are management and leadership, organizational culture, organizational structure and organizational processes/systems. The integration of these key drivers is essential for the implementation of strategy, leading to improved service delivery to various stakeholders. The report concludes that in order to approach strategy implementation in an integrated manner, the following should take place: (1) managers who are responsible for strategy implementation should also be involved in strategy formulation processes; (2) organizational culture should be changed to create a conducive environment for the managers to be motivated; (3) leadership and management should guide the vision and mission; (4) organizational processes/systems should be coordinated and integrated for efficiency and effectiveness
Thesis (M.A. (Business administration)) University of Limpopo, 2008
Keywords: Business strategy; Business planning; Strategic planning -- South Africa -- Limpopo